(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
Since the credit market is seriously dependent on socio-economic factors, this article presents an assessment of the socio-economic situation of the population living in the Orenburg region. Such indicators as the population as a whole, as well as individual economic groups, average per capita income are analyzed, the level of creditworthiness of the population is calculated, conclusions are drawn about the main effective directions of consumer lending in the region.